Legal analysis of the interaction between the state and citizens in the context of solid household waste regulation in the Republic of Kazakhstan - Abdizhami, A.Zh. (Karagandy University of the name of acad. E.A. Buketov, 2024)
In the modern world, the problem of waste management is becoming more urgent and requires society to constantly regulate and adopt effective legislative mechanisms. In the article, the authors consider an important aspect in this area — the interaction between the state and citizens in the context of waste management. The interaction of these entities plays a key role in creating an effective solid waste management system aimed at ensuring environmental safety and sustainable development of society through the analysis of regulatory legal acts, statistical data and good practices in this area. The article discusses several key problems related to solid waste management in Kazakhstan, including a lack of information for citizens (for example, it is not enough to publish materials on websites, they must be updated regularly), unavailability of infrastructure (sorting centers are located far from public accommodation, it is not possible to take garbage to specially designated places), low motivation (due to monthly utility bills for garbage collection, many people consider, that the relevant institutions should be engaged in the collection and sorting of solid household waste or do not understand the danger of consequences for the environment), inconsistencies in legislation have been identified (there are no mechanisms for imposing fines for nonsorting garbage, as abroad) and insufficient financing (if we do not have finances, whatever industry we take, we cannot achieve high results). In order to improve the situation in society, the need to develop mass educational programs related to garbage sorting, develop infrastructure related to the sorting of solid household waste, further reform legislation related to environmental and sustainable development, and focus on strategies to attract investors and funds to this industry was justified. In the article, based on the comprehensive directions adopted by the state to support citizens in the collection and sorting of solid household waste, we came to the conclusion of a settlement of the problem associated with waste recycling. A concrete solution to these problems is manifested in the definition of general directions of development in waste management.
Қазақстан Республикасындағы қатты тұрмыстық қалдықтарды реттеу жағдайындағы мемлекет пен азаматтардың өзара іс-қимылына құқықтық талдау
Правовой анализ взаимодействия государства и граждан в контексте регулирования твердых бытовых отходов в Республике Казахстан
Keywords: Environment; environmental legislation; the right to a favorable environment; waste; solid household waste; waste management; state regulation of waste; waste sorting; waste recycling; stimulation of waste sorting; environmental harm reduction; the role of citizens in waste sorting